IGF2 drives formation of ileal neuroendocrine tumors in patients and mice. Issue 3 (March 2020) - Contractor, Tanupriya; Clausen, Richard; Harris, Grant R; Rosenfeld, Jeffrey A; Carpizo, Darren R; Tang, Laura; Harris, Chris R
Abstract : By the strictest of definitions, a genetic driver of tumorigenesis should fulfill two criteria: it should be altered in a high percentage of patient tumors, and it should also be able to cause the same type of tumor to form in mice. No gene that fits either of these criteria has ever been found for ileal neuroendocrine tumors (I-NETs), which in humans are known for an unusual lack of recurrently mutated genes, and which have never been detected in mice. In the following report, we show that I-NETs can be generated by transgenic RT2 mice, which is a classic model for a genetically unrelated disease, pancreatic neuroendocrine tumors (PNETs). The ability of RT2 mice to generate I-NETs depended upon genetic background. I-NETs appeared in a B6AF1 genetic background, but not in a B6 background nor even in an AB6F1 background. AB6F1 and B6AF1 have identical nuclear DNA but can potentially express different allelic forms of imprinted genes. This led us to test human I-NETs for loss of imprinting, and we discovered that the IGF2 gene showed loss of imprinting and increased expression in the I-NETs of 57% of patients. By increasing IGF2 activity genetically, I-NETs could be produced by RT2 mice in a B6 genetic background, which otherwise never developed I-NETs. The facts that IGF2 is altered in a high percentage of patients with I-NETs and that I-NETs can form in mice that have elevated IGF2 activity, define IGF2 as the first genetic driver of ileal neuroendocrine tumorigenesis.